Multiple-Mixing-Cell Model for Calculation of Minimum Miscibility Pressure Controlled by Tie-Line Length. (6th March 2020) - Yang, FuLin; Yu, Peng; Zhang, Xue
Abstract : A simple and robust algorithm has been developed to calculate the minimum miscibility pressure (MMP), which is considered one of the crucial and essential design parameters of miscible gas injection projects for enhanced oil recovery (EOR). This algorithm is to track all tie-line lengths through the cell-cell calculation by the minimum distance function for the prediction of MMP. The MMP is the pressure at which any one of all key tie-line lengths becomes zero. To verify the accuracy of the revised MMC algorithm for determining MMP, several examples taken from the published literature have been examined. The calculation results of our revised MMC algorithm show excellent agreement with those estimated by MOC, MMC, and slim-tube experiments, which are found to be reliable within acceptable accuracy (4.53%-0.50%).